Characterization of Nkx6-2-Derived Neocortical Interneuron Lineages - Sousa, Vitor H. (Oxford University Press, 2009)
Ventral telencephalic progenitors expressing the homeodomain transcription factor Nkx6-2 have been shown to give rise to a multitude of cortical interneuron subtypes usually associated with origin in either the medial ganglionic eminence or the caudal ganglionic eminence. The function of Nkx6-2 in directing the fate of those progenitors has, however, not been thoroughly analyzed. We used a combination of genetic inducible fate mapping and in vivo loss-of-function to analyze the requirement of Nkx6-2 in determining the fate of cortical interneurons. We have found that interneuron subtypes are born with a characteristic temporal pattern. Furthermore, we extend the characterization of interneurons from the Nkx6-2 lineage through the application of electrophysiological methods. Analysis of these populations in Nkx6-2 null mice suggests that there is a small and partially penetrant loss of delayed non-fast spiking somatostatin/calretinin double positive cortical interneurons in the absence of Nkx6-2 gene function.